Fin de régime et migrations en Libye.Les enseignements juridiques d’un pays en feu - Delphine Perrin (L’Année du Maghreb)
The war in Libya and the resulting departure of hundreds of thousands of foreigners offer a new perspective of the Libyan migratory reality and the policies it has given rise to in recent years. A labor market in need of an ever more diverse foreign labor force, Libya enjoyed a migration diplomacy, reflected in a versatile and proclamatory right. In relation to Europe, Libya skillfully turned migrants on its soil into a spectrum in transit against which the – already isolated – Italian outpost could not resist, while the reform of its immigration law plunged most of them into irregularity. Weakened by its irrational migration policies, the EU has yielded to the Libyan “pirate diplomacy” and gradually given up all principles and legal safeguards to engage in ad hoc cooperation, mainly delegated to Italy, to contain the migration to the south of the Mediterranean.